2007
DOI: 10.1038/sj.eye.6702860
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyaluronidase on ultrasound-measured dispersal of local anaesthetic following sub-Tenon injection

Abstract: Purpose To determine by B-scan ultrasonography if the addition of hyaluronidase affects the dispersal of anaesthetic fluid after sub-Tenon's injection. Design Single-centre prospective randomised double-blind study. Materials and methods We performed a trial in 19 patients who were randomised to receive 5 ml of lidocaine 2% alone, or with hyaluronidase 15 IU/ml. A pre-anaesthetic B-scan ultrasound was performed followed by a standard infero-nasal sub-Tenon's injection. Further B-scan ultrasound studies were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
(12 reference statements)
1
16
0
Order By: Relevance
“…Additional clinical studies also have reported the overall safety and tolerability of rHuPH20 coadministration with other agents. [40][41][42] It should be noted that there is no long-term, repeat dose exposure to rHuPH20 data available; an ongoing 3-month × 3-month crossover study comparing regular insulin-PH20 to insulin lispro in 48 type 1 diabetic subjects did not uncover any safety or tolerability signals at the time of an interim safety analysis among the 22 subjects receiving regular insulin-PH20 (data not shown); longer term data in larger numbers of subjects will be needed to better address this question.…”
Section: Clinical Pharmacology Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional clinical studies also have reported the overall safety and tolerability of rHuPH20 coadministration with other agents. [40][41][42] It should be noted that there is no long-term, repeat dose exposure to rHuPH20 data available; an ongoing 3-month × 3-month crossover study comparing regular insulin-PH20 to insulin lispro in 48 type 1 diabetic subjects did not uncover any safety or tolerability signals at the time of an interim safety analysis among the 22 subjects receiving regular insulin-PH20 (data not shown); longer term data in larger numbers of subjects will be needed to better address this question.…”
Section: Clinical Pharmacology Studiesmentioning
confidence: 99%
“…10,23,[38][39][40][41][42] The clinical safety and tolerability of hyaluronidase, which was first reported by Burket and Gyorgy in 1949, 38 have been established further with over 6 decades of use. 10,23,[39][40][41][42] Clinical history demonstrates the increased dispersion and faster absorption of a broad range of drugs and fluids administered with hyaluronidase products.…”
Section: History Of Hyaluronidase Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Following sub-Tenon injection, local anaesthetic solution has been demonstrated to accumulate in the sub-Tenon space, behind the globe, which is traversed by short and long ciliary nerves (Khandwala et al 2008).…”
mentioning
confidence: 99%